Development of platelets during steady state and inflammation. Issue 5 (24th February 2017) - Müller‐Newen, Gerhard; Stope, Matthias B.; Kraus, Thomas; Ziegler, Patrick
Abstract : Review on how inflammatory signals are integrated into early megakaryopoiesis in order to replenish consumed platelets during inflammatory conditions. Abstract : Megakaryocytes (MK) are the sole source of platelets in the body. They develop from lineage‐committed hematopoietic stem and progenitor cells (HSPCs) via intermediate cells, which differ in morphology, size, ploidy, and surface phenotype. Development and maturation of MKs is governed by different transcription factors, including GATA‐1, E26 transformation‐specific transcription factor (ETS) family members, nuclear factor erythroid 2 transcription factor (NF‐E2), and STAT3. During such challenges as acute inflammation, platelets are consumed in high numbers and must be replenished to secure survival of the host. This is achieved by integration of inflammatory signals into early MK development and depends on the STAT1‐mediated enhanced translation of transcripts in stem cell‐like megakaryocyte progenitors. Here, we review recent developments, which highlight the impact of inflammation on the development of platelets from HSPCs.